Mathematics
         
语言:中文    Language:English
On line Solution of Monovariate Equation:
    Input any unary equation directly, and then click the "Next" button to obtain the solution of the equation.
    It supports equations that contain mathematical functions.
    Current location:Equations > Monovariate Equation > The history of univariate equation calculation > Answer

    Overview: 1 questions will be solved this time.Among them
           ☆1 equations

[ 1/1 Equation]
    Work: Find the solution of equation m+(m-3)/2 = 3-(2m-1)/3 .
    Question type: Equation
    Solution:Original question:
      m + ( m 3) ÷ 2 = 3(2 m 1) ÷ 3
    Remove the bracket on the left of the equation:
     Left side of the equation = m + m ×
1
2
3 ×
1
2
                                             = m + m ×
1
2
3
2
                                             =
3
2
m
3
2
    The equation is transformed into :
     
3
2
m
3
2
= 3(2 m 1) ÷ 3
    Remove the bracket on the right of the equation:
     Right side of the equation = 32 m ×
1
3
+ 1 ×
1
3
                                               = 3
2
3
m +
1
3
                                               =
10
3
2
3
m
    The equation is transformed into :
     
3
2
m
3
2
=
10
3
2
3
m

    Transposition :
     
3
2
m +
2
3
m =
10
3
+
3
2

    Combine the items on the left of the equation:
     
13
6
m =
10
3
+
3
2

    Combine the items on the right of the equation:
     
13
6
m =
29
6

    The coefficient of the unknown number is reduced to 1 :
      m =
29
6
÷
13
6
        =
29
6
×
6
13
        = 29 ×
1
13

    We obtained :
      m =
29
13
    This is the solution of the equation.

    Convert the result to decimal form :
      m = 2.230769



Your problem has not been solved here? Please go to the Hot Problems section!





  New addition:Lenders ToolBox module(Specific location:Math OP > Lenders ToolBox ),welcome。